Industrial Development Report 2018 - United Nations Industrial Development Organization (United Nations, 2018)
Too often, demand is not considered when discussing industrial development. But the fact that manufacturing consumption is the most visible result of industrial development, and one of its most important drivers, calls for attention. This report argues that under the right set of conditions the consumption of manufacturing goods can set in motion a virtuous circle of income creation, demand diversification and long-run development. How? By providing new and better goods that become cheaper through time, industrial development creates real incomes for all which in turn lead to changes in consumption patterns that stimulate further creation of new and better goods restarting the circle. This circle, however, is not necessarily socially inclusive or environmentally sustainable, thus calling for specific policies to achieve these important goals. This report examines identifies the main challenges and opportunities that arise from them taking into account the sustainable development agenda.